International investment law and history - Schill, Stephan W., 1976-; Tams, Christian J.; Hofmann, Rainer, 1953- (Frankfurt investment and economic law, 2018)
Historiographical approaches in international investment law scholarship are becoming ever more important. This insightful book combines perspectives from a range of expert international law scholars who explore ways in which using a broad variety of methods in historical research can lead to a better understanding of international investment law. International Investment Law and History critically evaluates the use of historical analysis in international investment law. It examines the various roles that historical arguments play in interpreting investment treaties, resolving investor-state disputes, and justifying or criticizing the current system of investment protection. This book is the first in-depth study on the methodological challenges and benefits of historical approaches in international investment law. As such, it is a vital tool for scholars and practitioners in the field who wish to understand ways in which to use historical research and analysis to improve and redefine international investment law.